2006
DOI: 10.4141/p06-030
|View full text |Cite
|
Sign up to set email alerts
|

The Biology of Invasive Alien Plants in Canada. 6. Berteroa incana (L.) DC

Abstract: Warwick, S. I. and Francis A. 2006. The Biology of Invasive Alien Plants in Canada. 6. Berteroa incana (L.) DC. Can. J. Plant Sci. 86: 1297-1309. The cruciferous weed Berteroa incana, hoary alyssum, has been known in temperate North America since the late 19th century, but has recently begun to spread aggressively in upland and dry areas in the Great Lakes and western foothills regions of both Canada and the United States. It is an annual, winter annual to short-lived perennial and is considered an invasive we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Despite the fact that these species are predominantly wind-dispersed, dispersal via footwear and mowing machines have been reported as potential dispersal mechanisms for B . incana [115]. Unintended human-mediated dispersal by vehicles [116] or clothing attachment [117] was found to effectively disperse C .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that these species are predominantly wind-dispersed, dispersal via footwear and mowing machines have been reported as potential dispersal mechanisms for B . incana [115]. Unintended human-mediated dispersal by vehicles [116] or clothing attachment [117] was found to effectively disperse C .…”
Section: Discussionmentioning
confidence: 99%
“…incana and A. thaliana share the same mechanisms in carbon fixation because both of them are crucifers and C 3 plants (Warwick and Francis, 2006). As a spring ephemeral, B. incana is able to grow pretty well in the field at light intensities ranging from 200 to 1500 mol photons m −2 s −1 (Yuan et al, 2009) (see Fig.…”
Section: B Incana Grows Well At High Light Intensitiesmentioning
confidence: 97%
“…Berteroa incana (B. incana) is a spring ephemeral, which belongs to the family Brassicaceae. B. incana follows the C 3 pathway in photosynthesis and inhabits mostly in arid and sandy environments because of its xerophytic character (Warwick and Francis, 2006). In order to provide a fundamental basis for the mechanism whereby ephemerals acclimate to the changing light environments, especially under strong light conditions, Chl a fluorescence measurements are used to study the photosynthetic characteristics of B. incana grown under arid field conditions and in the greenhouse under different growth irradiances.…”
Section: Introductionmentioning
confidence: 99%
“…Our results support other studies that showed herbicide applications during flowering and early seed formation can impede production of viable and germinable seeds across a variety of weedy species (Asghari and Evans 1992;Mashhadi and Evans 1986;McDaniel et al 2002;Nurse et al 2015). Because B. incana propagates only by seed (Warwick and Francis 2006), controlling viable seed production is critical for effective management. Table 3).…”
Section: Seed Viabilitymentioning
confidence: 99%
“…In greenhouse experiments, fertilization and mowing were not effective at reducing B. incana (Stopps 2012). Although somewhat effective in cropping systems, tilling is not a practical option in pastures (Warwick and Francis 2006), and there are no biocontrol agents for B. incana (Parkinson et al 2017). Additionally, there is limited information on chemical control of B. incana (Dutt et al 1983; Kust 1969; Richardson and Zandstra 2005), and no studies have been conducted in rangeland or grass pasture.…”
Section: Introductionmentioning
confidence: 99%